2010
DOI: 10.1124/dmd.109.029959
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Phase II Enzymes and Transporters in Futile Cycling: Influence of Multidrug Resistance-Associated Protein 2-Mediated Excretion of Estradiol 17β-d-Glucuronide and Its 3-Sulfate Metabolite on Net Sulfation in Perfused TRand Wistar Rat Liver Preparations

Abstract: ABSTRACT:The hepatic disposition of estradiol 17␤-D-glucuronide (E 2 17G), a substrate of the organic anion-transporting polypeptides Oatp1a1, Oatp1a4, and Oatp1b2, was investigated in Wistar and E 2 3S17G (11؋) in liver and reduced net sulfation (40 ؎ 6 from 77 ؎ 6% dose, P < 0.05) were observed at 2 h for the TR ؊ versus the Wistar rats. With use of a physiologically based pharmacokinetic model, analytical solutions for the areas under the curve for the precursor and metabolite were obtained to reveal how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Therefore, prediction of Fg for such compounds, which are often eliminated through phase II metabolism and subsequent excretion, is becoming essential. For anionic compounds, the interactions of conjugating enzymes with transporters have been increasingly recognized as an important process of elimination (Nies et al, 2008;Pang et al, 2009;Sun et al, 2010). Therefore, comprehensive studies including metabolism and transport are required.…”
Section: Intestinal and Hepatic Availabilities Of Ugt Substratesmentioning
confidence: 99%
“…Therefore, prediction of Fg for such compounds, which are often eliminated through phase II metabolism and subsequent excretion, is becoming essential. For anionic compounds, the interactions of conjugating enzymes with transporters have been increasingly recognized as an important process of elimination (Nies et al, 2008;Pang et al, 2009;Sun et al, 2010). Therefore, comprehensive studies including metabolism and transport are required.…”
Section: Intestinal and Hepatic Availabilities Of Ugt Substratesmentioning
confidence: 99%
“…Overall, decreased biliary excretion combined with increased glucuronidation led to significantly increased cellular accumulation of TG in TR -compared with WT rat SCH. Medium concentrations of TG also were increased in TR -rat SCH, consistent with increased glucuronidation and increased expression of the basolateral efflux transporter Mrp3 (Johnson et al, 2006;Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 70%
“…In rats, TS formation is four times faster in male rats compared with female rats, which is consistent with greater expression of Sult1a1 and Sult1e1 in male rats (Demyan et al, 1992;Liu and Klaassen, 1996). Interestingly, protein levels of hepatic Sult1a1 and Sult1e1 were comparable between WT and TR -rats (Johnson et al, 2006;Sun et al, 2010), and our in vitro metabolism study using S9 fractions from livers of WT and TR -rats revealed that TS formation rates were comparable. A decrease in net sulfation of estradiol-17 b-glucuronide (E 2 17G) reported in TR -rats was attributed to increased desulfation of estradiol-3-sulfate-17b-glucuronide (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations